Isolation and characterization of cellulose whiskers from kenaf (Hibiscus cannabinus L.) bast fibers - Zaini, Lukmanul Hakim; Jonoobi, Mehdi; Md. Tahir, Paridah; Karimi, Samaneh (Scientific Research Publishing, 2013)
Cellulose whiskers were isolated from kenaf (Hibiscus cannabinus L.) bast fibers via sulfuric acid and hydrochloric acid hydrolysis. Raw kenaf bast, NaOH treated, bleached fibers, sulfuric acid whiskers (SAW) and hydrochloric acid whiskers (HClW) morphology, functional groups, crystallinity, and thermal stability were characterized. The TEM images showed that the sulfuric acid and HCl whiskers have average diameters and length range of 3 nm and 100 - 500 nm, respectively. The FTIR study indicated that during the conversion process, most of the hemicellulose and almost all the lignin were removed by the NaOH and subsequent bleaching treatments. The crystallinity of HCl whiskers was found to be higher (84%) than that of sulfuric acid whiskers (72%). Thermogravimetric analysis indicated that HCl whiskers had better thermal stability than the sulfuric acid ones. In addition, a two-stage decomposition behavior was revealed by TGA in the sulfuric acid whiskers because of incorporation of the sulfate group with the cellulose crystals.